The effects of single versus mixed gender treatment for adolescent girls with ADHD - Babinski, Dara E. (2013)
OBJECTIVE: This study evaluated the social behavior of adolescents with ADHD in single and mixed gender treatment settings. METHOD: We collected ratings of social behavior (i.e., prosocial peer interactions, assertiveness, self-management, compliance, physical aggression, relational aggression) during single and mixed gender games within the Summer Treatment Program-Adolescent (STP-A) for 10 girls (mean age 13.17, 80% Hispanic) and 11 boys (mean age 12.89, 54.55% Hispanic). Counselors completed ratings immediately following 10 recreational periods for each adolescent they supervised (5 single gender games, 5 mixed gender games). Gender (female versus male) x setting (single versus mixed gender) ANOVAs were conducted. If a significant interaction emerged, post hoc tests were also conducted. RESULTS: Several gender by setting interactions emerged, suggesting that girls benefit more from single gender formats than mixed gender formats. Girls showed more assertiveness, self-management, and compliance in single compared to mixed gender settings. A somewhat different pattern of results emerged for boys, which showed more appropriate social behavior (i.e., self-management, compliance) and less inappropriate social behavior (i.e., physical and relational aggression) in mixed gender settings compared to single gender settings. CONCLUSIONS: In contrast to previous ADHD treatment studies, these findings suggest that gender may impact treatment response for adolescents. Therefore, it is important that future studies evaluate whether current treatments for ADHD are appropriate for girls with ADHD, and if gender-specific treatments are necessary to address the unique difficulties of adolescent girls with ADHD.